Mėnulio stereotipai lietuvių poezijoje - Kazlauskaitė, Rūta (Baltistica, 2009)
Stereotypes in perception of the Moon in Lithuanian poetryThe aim of the present article is to analyse and to discuss the linguistic expression and the semantic paradigm of the images of the Moon that have formed in Lithuanian poetry. The fragments of 124 poets’ 389 poems have been analysed.The Moon is perceived as an object that shines at night and changes its shape. These two features motivate the absolute majority of its names. The examples show that the main work of the Moon is to reflect the sunlight to the Earth (“to shine”). The expressive lunar phases most often used in poetry are a full moon and waning crescents. Natural surroundings of the Moon are not emphasized: place above the ground, time of manifestation, separation.The Moon and its light are metaphorically related to living beings, blooming plants, raw materials and handicraft ware, liquids, fire. A living being is firstly a human being, but it is not difficult to discern the signs of deity. Less frequent are zoomorphic, ornithomorphic and ichthyomorphic shapes.Stereotypes of the Moon are conditioned by the similarities of the compared object in brightness, light and/or form, less often in the position above and solitude. The surroundings of the Moon are shown as a closed space above the ground well known to humans. The basis of only few stereotypes is not nature but civilization.
Keywords: Lithuanian; poetry; stereotypes; Moon